(3adSajI (B- (3JYdjejI(B- (3faSjI (B- (3aSjhdhLjI (B- (3HjhejcGfjcjI (B- (3GOGQjIs - (3YHO GdQMeGf fHjdI GMeOs; (3acQj , Sdhi YR GdOjf s ((3GdbGgQIs (3OGQ GdacQ GdYQHjs, 2004)
(3GdGJOQjH GdQjGVj ef MjK gh (B- (3YedjI (B- (3ehVMG eOi TehdjJgG hcja CfgG JYJeO HOQLI cHjQI Ydi eLGdGJ eJYOO, h JJchf ef YOO cHjQ ef GdeJZjQGJ h GdeQGMd PGJi GdYdGbI GdeJOGNdI h GdeJHGOdI h GdJj jJhba cd efgG Ydi GdGNQi, MJi JJe eeGQSI JOQjHjI aYGdI ceG jgJe gPG GdcJGH HCf jDef GdeOQHhf ChdG (B: (3HCf aYGdjI GdeeGQSI GdJOQjHjI jLH Cf JYJeO HOQLI cHjQI Ydi eHGOF h CSS Ydhe GdQjGVI GdJWHjbjI(B. (3KGfjG (B: (3Cf GdeOQHjf ge GdeSDhdjf Yf GOGQI GdLhGfH GdeNJdaI dgPg GdYedjI h Jchjf GdGSJQGJjLjI GdaYGdI dJMSjf GdGOGA aj GdQjGVGJ ddGYH h ddaQjb eY GdGNP HYjf GdGYJHGQ Gf GdOGA GdQjGVj LRA ef gPg GdYedjI h Gf GdaYGdjI JQJHW GSGSG HcjajI JcGed h GOGQI gPg GdefXheI GdeYbOI dYedjI GdJOQjH GdQjGVjs
Keywords: (3GdJOQjH GdQjGVjs; (3GdQjGVI GdJWHjbjIs